(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
This analysis covers Bulgaria’s wood product industry over a period of 14 years. It uses quantitative techniques to assess production volumes, export and import trends and trade balance of wooden products. Certain key aspects such as the shift in economic policy or the change in market demand have also been examined in terms of their effects on the sector’s performance. Multiples methods of statistics are also used to detect the production and trade anomalies over time, and also major domestic and international events that may have caused a great shift in production dynamics. In mapping the development of Bulgaria’s wood product industries, the analysis identifies both the main’s determinants and constraints within the industry that can be used in strategic decision-making in the future by the stakeholders.